The influence of doctoral management and medical procedures on patient satisfaction: An analysis based on appointment and medical procedure data - Terangjaya Yadi Fakhruzein; Dewi Pramesti; Widadi Budi; Salsabila Riska Nadiya (BIO Web of Conferences)
The impact of medical procedures and physician management on patient satisfaction is investigated in this study. Physician experience, specialization, waiting time, and the length of medical procedures are the primary characteristics examined. Hospital appointment and procedure records were used to gather data, and waiting time and procedure length were used as stand-ins for patient satisfaction. Patient satisfaction is significantly impacted by waiting time, according to the results. There is a negative correlation between waiting time and satisfaction, particularly for specialists. Even though they have lengthier wait times, specialists and subspecialists nevertheless offer greater satisfaction than general practitioners. There were reduced wait times for doctors with five to ten years of experience. However, there was no discernible impact of the length of medical procedures on patient satisfaction. The main findings suggest that waiting time management is critical to improving patient satisfaction, while duration of medical procedures has no significant impact. Therefore, optimizing doctor scheduling and improving communication with patients should be considered.